2017
DOI: 10.1590/1806-9126-rbef-2017-0102
|View full text |Cite
|
Sign up to set email alerts
|

Laser cooling techniques: standard and alternated optical molasses

Abstract: The technique of laser cooling, whose basic idea was proposed in 1975 [1], provided the development of many important areas like high-resolution spectroscopy [2], atomic clocks [3] and quantum gases confined in magnetic or optical traps [4,5]. Among the techniques applied to cooling neutral atoms is the optical molasses [6] that will be explored in this work. Here we study the standard molasses and a new alternated molasses configuration, which consists of turning on just one pair of counter-propagating laser … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The number and density of trapped atoms in a vapour-cell Zeeman trap are investigated experimentally and theoretically, and it is shown that this quantity is affected by the laser beam sizes, laser intensities, laser detunings, and magnetic-field gradients [19]. The interaction of neutral atoms with the radiation force in OMs is studied using a semi-classical method of the laser-cooling concept [20]. Particularly, since the magnitude of the repulsive force depends on the laser intensity, the power of rescattered light limits the number of trapped atoms.…”
mentioning
confidence: 99%
“…The number and density of trapped atoms in a vapour-cell Zeeman trap are investigated experimentally and theoretically, and it is shown that this quantity is affected by the laser beam sizes, laser intensities, laser detunings, and magnetic-field gradients [19]. The interaction of neutral atoms with the radiation force in OMs is studied using a semi-classical method of the laser-cooling concept [20]. Particularly, since the magnitude of the repulsive force depends on the laser intensity, the power of rescattered light limits the number of trapped atoms.…”
mentioning
confidence: 99%